Peran generasi z dalam menjaga nilai toleransi dan multikulturalisme - Mas’ud, Moh. Roikhan (Maliki Interdisciplinary Journal, 2026)
Generation Z is a group of people who were born and raised in the era of rapid digital technology advancement and globalization. This situation places Generation Z in an important position in maintaining the values of tolerance and multiculturalism in Indonesia, a country rich in ethnic, religious, cultural, and linguistic diversity. This article aims to examine the role of Generation Z in fostering tolerant attitudes in social life while also addressing various forms of intolerance that develop through digital media. This study uses a literature review method by utilizing various references, such as journals, online news, and scientific articles related to tolerance and multiculturalism in Indonesia. The results of the discussion show that Generation Z makes significant contributions through the dissemination of educational content, the implementation of social campaigns, and active participation in cross-cultural and interfaith activities. However, the development of social media also presents challenges because it can become a medium for spreading hate speech and provocative information. Therefore, strengthening character education, improving digital literacy, and enhancing understanding of multicultural values are necessary so that Generation Z can act as agents of peace and maintain national unity within Indonesia’s diverse society.